Is metal fume fever a determinant of welding related respiratory symptoms and/or increased bronchial responsiveness? A longitudinal study. Issue 10 (16th September 2005) - El-Zein, M; Infante-Rivard, C; Malo, J-L; Gautrin, D
Abstract : Background: The current prospective study investigated the hypothesis of metal fume fever (MFF) being a predictor for the development of respiratory symptoms and functional abnormalities. Methods: The study consisted of a pre-exposure and two follow up assessments of 286 welding apprentices during an average period of 15 months. A respiratory and a systemic symptom questionnaire, skin prick tests to common allergens and metal salts, spirometry, and methacholine challenge tests were administered. Results: Developing at least one positive skin prick test to a metallic salt solution was found in 11.8% of apprentices. Possible MFF (at least one of fever, feelings of flu, general malaise, chills, dry cough, metallic taste, or shortness of breath) was reported by 39.2% of apprentices. The presence of at least one welding related respiratory symptom (cough, wheezing, or chest tightness) suggestive of welding related asthma was reported by 13.8%. MFF was significantly associated with these respiratory symptoms (OR = 4.92, 95% CI 2.10 to 11.52), after adjusting for age, atopy, smoking, physician diagnosed asthma, and symptoms of non-welding related asthma. Apprentices with possible MFF, and no welding related respiratory symptoms suggestive of welding related asthma at the first follow up, had an increased risk of developing the latter symptoms by the second follow up visit (OR = 7.4, 95% CI 1.97 to 27.45) compared with those not having MFF. MFF was not significantly associated with an increase in bronchial responsiveness. Conclusion: MFF could be a predictor for the development of respiratory symptoms but not for functional abnormalities in welders.